Catalytic effect of in situ formed Mg2Ni and REHx (RE: Ce and Y) on thermodynamics and kinetics of Mg-RE-Ni hydrogen storage alloy. (September 2020) - Yong, Hui; Guo, Shihai; Yuan, Zeming; Qi, Yan; Zhao, Dongliang; Zhang, Yanghuan
Abstract: To clarify the effect of Mg2 Ni and REHx (RE: Ce and Y) on the thermodynamics and kinetics of Mg-RE-Ni alloys, a series of quaternary Mg–Ce–Y–Ni alloys with different RE and Ni contents were prepared by vacuum induction melting. Their microstructure, phase composition, and the hydrogen storage performance were investigated by using X-ray diffraction, scanning electron microscopy, high-resolution transmission electron microscopy, and Sievert's-type apparatus. The results indicate that the alloys are mainly composed of the REMgx phase, Mg2 Ni phase, and Mg phase, and the change of RE and Ni contents did not change the phase composition but affected the phase content and micro-eutectic morphology. After hydrogenation, the REMg x phase was decomposed into irreversible REH x grains and dispersed in the MgH2 matrix together with Mg2 NiH4 grains, which result in an outstanding kinetics performance. By contrast, the REH x phase is more favorable for hydrogen absorption, while Mg2 NiH4 is more favorable for hydrogen desorption, which attributes to their independent catalytic mechanisms. Also, the finer microstructure induced a slight decrease in thermodynamics. The Ni5 alloy has an optimal comprehensive hydrogen storage performance, which can absorb 5 wt% H2 within 2 min and release the same amount of hydrogen at 300 °C within 10 min. Highlights: Hydrogen storage properties of Ce–Mg–Y–Ni nano-composite are investigated. Catalytic effects of the in situ formed Mg2 NiH4 and (Ce, Y)H2.73 are evaluated. Fine eutectic structure can induce a slight decrease in thermodynamics. Rate-limiting step of desorption hydrogen can be transformed by adding Ni. Mg90 (Ce, Y)5 Ni5 only takes 10 min to release more than 5 wt%H2 at 300 °C.